KONSEP MAQĀSHID SYARIA THE CONCEPT OF MAQĀSHID SYARIAH AS-SYĀṬIBY. in The Book Al Muwāfaqāth As-Syāṭiby - Khalil Al Farahidy (Universitas Islam Negeri Ar-Raniry, 2022)
As Syātiby is known as the father of Sharia maqāṣid science. This is because of what he wrote in his book Al-Muwāfaqāt. He outlined the concept of Allāh's intent and purpose in implementing the Shari'a. And what he put in his book can be easily understood by his readers, because it is written in neat and orderly divisions. He divided the discussion of objectives into two discussions. The first is Maqāshid Syari' or Allāh in establishing the Shari'a, namely for the good of mankind, and the second is Maqāshid Mukallaf or servant who must be in accordance with and not contradict Maqāṣid Syari'.